Sustainability Agenda for the Pantanal Wetland: Perspectives on a Collaborative Interface for Science, Policy, and Decision-Making. (September 2019) - Tomas, Walfrido M.; de Oliveira Roque, Fabio; Morato, Ronaldo G.; Medici, Patricia Emilia; Chiaravalloti, Rafael M.; Tortato, Fernando R.; Penha, Jerry M. F.; Izzo, Thiago J.; Garcia, Leticia C.; Lourival, Reinaldo F. F.; Girard, Pierre; Albuquerque, Nelson R.; et al.
Building bridges between environmental and political agendas is essential nowadays in face of the increasing human pressure on natural environments, including wetlands. Wetlands provide critical ecosystem services for humanity and can generate a considerable direct or indirect income to the local communities. To meet many of the sustainable development goals, we need to move our trajectory from the current environmental destructive development to a wiser wetland use. The current article contain a proposed agenda for the Pantanal aiming the improvement of public policy for conservation in the Pantanal, one of the largest, most diverse, and continuous inland wetland in the world. We suggest and discuss a list of 11 essential interfaces between science, policy, and development in region linked to the proposed agenda. We believe that a functional science network can booster the collaborative capability to generate creative ideas and solutions to address the big challenges faced by the Pantanal wetland.